derivative y=sin(e^(3x-x^2))?

show how

### 1 Answer | Add Yours

You need to use chain rule to find derivative of function.

The chain rule tells that you need to differentiate with respect to x, from outside toward inside, such that:

`dy/dx = (sin(e^(3x-x^2)))'*(e^(3x-x^2))'*(3x-x^2)'`

`dy/dx = (cos(e^(3x-x^2)))*(e^(3x-x^2))*(3- 2x)`

**Hence, the derivative of function is `dy/dx = (3- 2x)*(e^(3x-x^2))*(cos(e^(3x-x^2)))` **

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes